Biochemical and Molecular Characterization of Pichia pastoris Cells Expressing Multiple TMOF Genes (tmfA) for Mosquito Larval Control - Borovsky, Dov; Nauwelaers, Sabine; Shatters, Robert (Frontiers in Physiology, 2020)
Trypsin modulating oostatic factor (TMOF), a decapeptide hormone synthesized by female mosquito ovaries, ganglia and the central nervous system of Aedes Aegypti, terminates trypsin biosynthesis in larvae and blood-fed female mosquitoes. Earlier, TMOF was cloned and expressed as a single copy in Chlorella dessicata and in Saccharomyces cerevisiae cells as a potential larvicide. Here we report the use of a methylotrophic yeast cells, Pichia pastoris, that efficiently express multi copies of heterologous proteins, that are readily ingested by mosquito larvae. Pichia pastoris was engineered using pPICZB (Invitrogen, CA) and 2 genes: gfp-tmfA and tmfA inserted between KpnI and XbaI in the multiple cloning site. The plasmid carries a strong AOXI promoter and P. pastoris KM71 and KM71H cells were transformed by homologous recombination. The synthesis of GFP-TMOF was followed using UV and clones were analyzed using southern and Northern blot analyses. Cloning tmfA into KM71H and selection on high Zeocin concentration (2.0 mg/mL) identified a clone that carried 10 copies of tmfA. A comparison between a single and high copy (10 genes) insertions using Northern blot analyses showed that a tmfA transcript was highly expressed even after 120 h. SDS-PAGE analysis of KM71 cells transformed with gfp-tmfA identified a protein band that ran at the expected Mr of 31 kDa. ELISA analysis of the recombinant cells showed that 1.65x108 and 8.27x107 cells produce 229 and 114 nM of TMOF, respectively and caused 100% larval mortality when fed to groups of 5 larvae in 25 mL water. These results indicate that the recombinant P. pastoris cells could be used in the future in the marsh to control mosquito populations.